Flood Susceptibility Index Analysis using Overlay Method and GIS-based - Irmawati, Viviana; Cahyono , Ongko; Mujiyo; Maro'ah, Siti; Istiqomah, Nanda Mei; Romadhon, Muhammad Rizky (Universitas Pendidikan Ganesha, 2023)
High rainfall caused the overflow of the Wiroko river, causing flooding in Nguntoronadi. This study aims to analyze flood potential, provide evaluation and recommendations on areas that have high flood suscetibility. Type of research is quantitative descriptive by using the overlay method of scoring land characteristics that affect environmental conditions. Land characteristics are rainfall, altitude, slope, soil type and land use. The characteristics of the land are overlayed using the ArcGIS application to determine a map of flood susceptibility index, and the data were analyzed using descriptive methods. The result found three categories of flood susceptibility indexes: low, medium, and high. The study revealed a total area flood susceptibility of 6566.52 ha, with 33.79% having high flood susceptibility. The potential for high flood vulnerability is found in lowland, high rainfall and open land use. Areas which has a high flood susceptibility by improving river flow, drainage and terraces in rice fields. The high flood susceptibiity caused by rainfall, lowland and low vegetation as well as high human populations.